KEMAMPUAN BERPIKIR TINGKAT TINGGI DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS VII SMP ISLAM TERPADU (IT) NURUL HASAN MENGGUNAKAN LESSON STUDY - Amir, Johar; Sasmayunita, Sasmayunita (SOSCIED, 2023)
The purpose of this research is to describe the ability of higher order thinking in Indonesian language learning of seventh grade students of Nurul Hasan Integrated Islamic Junior High School (IT) using Lesson Study. The method used in this research is descriptive quantitative research method. The data in this study are in the form of test results of higher-order thinking skills using Lesson Study, observation data and interview data of VII grade teachers of Nurul Hasan Integrated Islamic Junior High School (IT). There are two types of data in the research, namely (1) primary data in the form of observation and interview results and (2) secondary data in the form of test results of higher order thinking skills using Lesson Study. The data analysis technique used in this research is quantitative descriptive analysis technique. Based on the data analysis of the results of this study, on the learning test of higher order thinking skills using Lesson Study students have been able to develop the ability to think critically to solve problems in learning through C3 remembering, C4 analyzing, C5 creating or inventing, and C6 high level thinking. The results showed that students can meet the high-level thinking skills seen from the way students remember, then analyze to find out differences in relevant things, can organize information and can connect information in a concept at the creation stage, students can recreate the preparation of official letters and personal letters well in accordance with the steps of letter writing.